GOVERNMENT SYSTEM OF KHULAFA AL-RASYIDIN An Analysis of Governmental Implementation Principles - Zulkarnaini, Zulkarnaini (STKIP An-Nur, 2019)
Khulafa Al-Rashidin's government was centered in Medina by using the principles listed in the Qur'an, and getting direct guidance from the Prophet. The principles that were run had been broken the system of Byzantine and Roman patterns. Deliberation that is full of freedom, not dichotomized or the message of the authorities, zuhud officials work to be accountable to God for the benefit of the people, just as the main goal without pseudo tradition that benefits the authorities. The principle of trust is the nature of leadership, so that human values emerge in state enforcement.Keywords: Government system, Khulafa Al-Rasyidin